Building Spring 2 Enterprise Applications - Ladd, Seth.; Smeets, Bram.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2007)
Spring has made a remarkable rise in popularity since its conception in 2002. Many users have found the lightweight, open-source Spring Framework 2.x ideal for building their applications in Java EE environments. Written by Interface21, Building Spring 2 Enterprise Applications will take developers through the following: Covers the first steps of using Spring while discussing the relevant technologies that Spring can be integrated with, what to be aware of, and how working with Spring makes them easier to use Focuses on the most useful features of Spring, including persistence and transaction management as well as the complete Spring web tools portfolio Introduces three-tier application design and how to test these designs.
A Gentle Introduction to the Spring Framework -- The Core Container -- Aspect-Oriented Programming -- Spring AOP 2.0 -- to Data Access -- Persistence with JDBC -- Transaction Management -- Spring MVC -- View Technologies -- Testing.
Keywords: Java (Computer program language).; Software engineering; Java; Software Engineering/Programming and Operating Systems